(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2024)
Fishermen in Labetawi village are part of the community living in the coastal area of Difur, North Dulah district, Tual City. This community service activity aims to make fishermen understand the importance of simple accounting and financial reporting as well as the separation of business and personal finances. Almost all fishermen in Labetawi village do not carry out financial recording activities. Community service was carried out by a team of lecturers from the Fisheries Agribusiness study program at the Tual State Fisheries Polytechnic, participants involved as many as 12 fishermen. The implementation method includes three stages, namely: (1) Survey, (2) Counseling and training, and (3) Evaluation. The results of this activity show a positive response from fishermen with a change in understanding of the benefits of routine accounting and separating business finance and household spending, making it easier to control business finances.